PEMODELAN SALURAN SUNGAI BAWAH TANAH GOA SALEH PADA MORFOLOGI KARST DAERAH PATTUNUANGASUE KABUPATEN MAROS MENGGUNAKAN METODE GEOLISTRIK - Ivan Taslim (Akademika, 2017)
This study aimed to identify potential subsurface water resources (underground river in Saleh Cave) on the Maros karst morphology. Identification of an underground river channel at Saleh Cave using resistivity measurements geoelectric method Wenner-Schlumberger configuration compiled with Saleh Cave dimensional mapping data, as well as muscular and topographical measurements. Geoelectric measurement consists of 9 tracks, acquired 2D and 3D resistivity cross-section shows the flow of the cave identified through the high resistivity range ρ> 2000 Ωm. Goa Saleh has a long corridor about 200m, where an underground river channel identified at a depth of 84-110 meters above sea level trending N320oE or leads from the Southeast to the Northwest. This is consist with the results of measurements of the fracture pattern (strike / dip) in the study site showing the same pattern of dominant fractures trending with underground streams in Saleh Cave. Compilation method used in this research can identify potential water resources that located beneath the surface karst morphology. Penelitian ini dimaksudkan untuk mengidentifikasi potensi sumber daya air bawah permukaan (sungai bawah tanah di Goa Saleh) pada morfologi karst Maros.Identifikasisaluran sungai bawah tanahGoa Saleh menggunakan pengukuran resistivitas metode geolistrik konfigurasi Wenner-Schlumberger dikompilasikan dengan data pemetaan dimensi Goa Saleh, serta pengukuran kekar dan pemetaan topografi.Pengukuran geolistrik terdiri dari 9 lintasan, diperoleh penampang resistivitas 2D dan 3D menunjukkan alur Goa teridentifikasi melalui harga resistivitas yang tinggi berkisar ρ>2000 Ωm. Goa Saleh memiliki panjang lorong sekitar 200m,dimana saluran sungai bawah tanah teridentifikasi di kedalaman 84-110 mdpl berarahN320oE ataumengarah dari Tenggara ke Barat laut. Hal ini sesuai dengan hasil pengukuran pola rekahan (strike/dip) di lokasi penelitian yang menunjukkan pola rekahan dominan berarah sama dengan aliran sungai bawah tanah di GoaSaleh. Kompilasi metode yang digunakan dalam penelitian ini dapat mengidentifikasi potensi sumber daya air yang terletak di bawah permukaan pada morfologi karst.